Rebranding of Crispy Seasoned Flour Produced by UD. LIBAS to Improve The Product Quality - Yunus, Muhammad; Wibowo, Yuli; Nurhayati, N. (JURNAL AGROTEKNOLOGI, 2025)
Crispy chicken and crispy mushrooms are examples of processed products using crispy seasoned flour. There are many spice flour producers, from small, medium, and large to micro industries. UD. LIBAS is one of the producers of crispy seasoning flour on a home industry scale (MSMEs). This research aims to improve the quality of “IIBAS” crispy seasoned flour through product rebranding. The research stages that be carried out are the process of data collection, analysis, and interpretation to achieve the research objectives. The existing brand of crispy seasoning flour "IIBAS" includes main elements such as visual identity, product excellence and the values it promotes. Visual identity includes a logo, attractive packaging, tagline, and color choices that reflect the value and quality of the product. The brand positioning of "IIBAS" crispy seasoned flour includes superior taste and a more affordable price compared to competitors. Important attributes of "IIBAS" crispy seasoned flour include ease of reading information on packaging and product distribution, which is a top priority for improvement. The level of consumer satisfaction towards "IIBAS" crispy seasoned flour reached 79.42% (satisfied category). Thus, it is hoped that this branding will increase the value of UD. LIBAS's crispy seasoned flour products and increase market share and sales turnover, thereby increasing the profits of the MSME producers. Keywords: branding, crispy, logo, MSMEs